THE IMPACT OF THE CORONAVIRUS PANDEMIC ON MACROECONOMIC INDICATORS: ANALYSIS USING A SYSTEM-DYNAMIC APPROACH - Bitkova, Tetiana; Tretiak, Viktoriia (Social Economics, 2021)
The article considers theoretical provisions concerning the direct and indirect impact of epidemics / pandemics on the macroeconomic indicators of different countries. The aim of the study is to study how the pandemic affects macroeconomic indicators and the scale of this impact using a system-dynamic concept of simulation to assess long-term trends in the analyzed processes - including combined dynamics and interactions of demographic, epidemic and economic indicators. In particular, we have analyzed and compared supply and demand shocks and economic losses associated with epidemics of different years and study the assumptions of classical compartmental models of epidemics (in particular SARS and SEIR ones) and the experience of system-dynamics concept using in simulating infections spread. The article presents the epidemic and economic situation in Ukraine in 2020-2021. We’ve evaluated the impact of infection spread on demographic indicators and have determined the correlation of the pandemic with the fall of Ukraine’s GDP in percentage to the same period of the previous year, in particular during the first lockdown in March-April 2020. Extension of SEIR model assumptions allowed us to build a demographic-epidemic system-dynamic model, which aggregated results were used in economic model. Both models are implemented in Vensim PLE. The control run results show a high accuracy of real processes reflection. In the economic model the GDP indicator is calculated during the model run, using a dynamized Cobb-Douglus production function, which parameters were estimated on the basis of the real data of Ukraine. The results of the economic model fairly accurately reflect the dynamics of population, capital investment and GDP per capita (the correlation coefficient of model and real data is 0.995). We consider that the main areas of experimentation with the model and of its use in decisions support are forecasting of macroeconomic indicators depending on different scenarios of the Covid-19 pandemic in Ukraine and on measures of its containment.